Preferences of customers in selecting clothing as a brand: A quantitative analysis on Bonanza. - Farooqui, Raheel; Ali, Sheikh Muhammad; Abbas, Mehdi (The journal of contemporary issues in business and government, 2021)
In this study we examined the relationship between the impact of style, price and quality on consumer perception. I used a survey technique and taken 100 samples from Kasbit Institute in Karachi and prioritized by SPSS. I used correlation and regression technique to find out the relationship between variables. The empirical findings suggest that there is a significance relationship exists between perception and style and there is an insignificance relationship between pricing, qualities on consumer perception. The implications of the study are that a company should better manage their pricing and quality factors with the customers as a competitive policy in informal clothing marketplace. The weak side of the study is that it is limited to a single industry of Fashion clothing industry.